Recontextualization of Ta’zir in the World of Education: Bridging Islamic Values, Children's Rights, and Pedagogical Practices - Yuniarti, Diah Retna; Sahid, M.; Faisal, Bagus Imam (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This article explores the relevance and reformulation of the concept of taʿzir in contemporary Islamic education, particularly in the context of the intersection between Islamic disciplinary traditions and modern human rights frameworks. Amid concerns about the harmfulness of punitive practices for children, this article highlights the importance of understanding taʿzir not merely as a means of physical or verbal punishment, but also as part of an ethical, contextual, and transformative pedagogical approach. Drawing on classical literature, educational theory, international law, and case studies from various Islamic educational institutions, this article argues that taʿzir has the flexibility to be reinterpreted within the framework of tarbiyah, the holistic development of students’ morals, spirituality, and intellectuality. This approach is in line with the principles of maqasid al-shariʿah and global child protection norms. This article proposes a model of taʿzir pedagogy based on compassion, justice, and empathy, and encourages synergy between stakeholders to create a non-violent and culturally relevant school discipline system. Thus, renewing taʿzir does not mean abandoning the legacy of tradition, but rather affirming it through a more humane and sustainable interpretation for the best interests of children in contemporary education.